Prevalence of Missed Canals and Their Association with Apical Periodontitis in Posterior Endodontically Treated Teeth: A CBCT Study - Mohammed Mashyakhy; Fatimah Ali Hadi; Hashimah Alhassan Alhazmi; Rawan Ali Alfaifi; Fatimah Saleem Alabsi; Hashim Bajawi; Mazen Alkahtany; Abdulaziz AbuMelha (Hindawi Limited, 2021)
Background. This study aimed to assess the prevalence of missed canals in endodontically treated teeth and their association with apical periodontitis in a Saudi Arabian population using CBCT. Materials and Methods. A total of 208 CBCT radiographs were investigated. For each tooth, radiographs of axial, coronal, and sagittal segments were acquired to appraise the external as well as the internal structure of the root canal system and apical area. In root canal-treated teeth, unfilled canals appearing from the cementoenamel junction to the apex were defined as missed untreated canals; and a periapical lesion was considered when disruption of the lamina dura was detected, and the low-density area associated with the radiographic apex was at least twice the width of the periodontal ligament space. The data were presented as frequencies and percentages. The Z-test was used to analyze the differences in proportions with the significance level set at P value <0.05. Results. The overall prevalence of missed canals among endodontically treated teeth was 18%. The prevalence of missed canals was higher in maxillary first molars with 40.6%. The overall prevalence of apical periodontitis among teeth with missed canals was 90%. It was 84.2% in the maxilla and 100% in the mandible. The second mesiobuccal canal in the maxillary first molars and mesiobuccal and distobuccal canals in mandibular teeth were the most missed canals. Conclusion. Apical periodontitis in root canal-treated teeth with missed canals was high (90%), with most identified missed canals in maxillary and mandibular first molars.